Innovative economic, social, and environmental practices for progressing future sustainability - Goi, Chai Lee, 1976- (Engineering Science Reference, 2022)
"This book explores the current practice in economic, social, and environmental sustainable development, which continues to prove its importance in our lives as it affects all aspects of them"--